Telerehabilitation for Total Hip and Knee Arthroplasty Patients: A Pilot Series with High Patient Satisfaction. Issue 3 (October 2019) - Kuether, Justin; Moore, Anne; Kahan, Joseph; Martucci, Joseph; Messina, Tara; Perreault, Roland; Sembler, Robert; Tarutis, John; Zazulak, Bohdanna; Rubin, Lee E.; O'Connor, Mary I.
Background: The demand for total hip and total knee arthroplasty in the USA is projected to increase significantly. Traditionally, face-to-face physical therapy has been an essential component of recovery in patients after total joint arthroplasty. Emerging technology allows telerehabilitation, or virtual physical therapy, which may reduce costs and increase standardization, but its effects on outcomes are not known. Questions/Purpose: We sought to review our initial experience using a telerehabilitation protocol for patients after primary total hip or total knee arthroplasty. Methods: In this pilot study, we retrospectively compared our first 40 telerehabilitation patients after a primary total hip or knee arthroplasty with a historical cohort or literature referenced values and evaluated (1) readmission rates at 90 days, (2) emergency department visits, (3) patient-reported outcome scores, (4) incidence of closed knee manipulation within 90 days of primary total knee arthroplasty, and (5) patient satisfaction surveys. Results: We observed no increase in the telerehabilitation group at 90 days in readmissions, emergency department visits, or closed knee manipulations. Accuracy of telerehabilitation exercises performed was 92%. Patient-reported outcome scores showed improvements comparable with traditional therapy. Extremely high patient satisfaction scores were reported with the telerehabilitation protocol. Conclusion: Our early experience demonstrates the feasibility of implementing a telerehabilitation program following primary total hip or knee arthroplasty without compromising clinical quality and with high patient satisfaction.